CANVA SEBAGAI MEDIA PEMBELAJARAN PADA MATA PELAJARAN DASAR LISTRIK DAN ELEKTRONIKA - Rahma Elvira Tanjung; Delsina Faiza (Voteteknika (Vocational Teknik Elektronika dan Informatika), 2019)
This research was conducted to find out the feasibility of using canva learning media in Basic Electrical and Electronics subjects in class X Cooling and Air Conditioning Engineering at SMK Negeri 3 Pariaman in the academic year 2018/2019. The research method used is the research development of the Instructional Development Institute. The research instrument used was a questionnaire. Respondents in the questionnaire were experts, teachers, and students. In canva learning media, the validity, reliability and practicality of the media are tested. Based on the results of validation by experts and teachers, the average value of validation is 0.83 which is at the validity value of ≥0.667, so it is in the valid category. In the media reliability test, the Cronbach's Alpha value was 0.731, so the criteria for media reliability were in high criteria. In the practicality test of the media by teachers and students, the average values were 90% and 86% respectively, so the practicality category of the media was in the very practical category. Based on the results of the three tests it can be seen that canva learning media is feasible to use in the learning processKeywords: Canva Learning Media, Media Validity, Media Reliability, Media Practicality.